Chloroplatinum(II) complex-modified MWCNTs paste electrode for electrochemical determination of mercury in skin lightening cosmetics. (1st November 2017) - Isa, Illyas Md; Saidin, Mohamad Idris; Ahmad, Mustaffa; Hashim, Norhayati; Bakar, Suriani Abu; Ali, Noorshida Mohd; M.Si, Suyanta
Graphical abstract: Abstract: The chemically modified multiwalled carbon nanotubes (MWCNTs) paste electrode with chloroplatinum(II) complex for the determination of mercury is presented. The chloroplatinum(II) complex was characterized by nuclear magnetic resonance spectroscopy (NMR), Fourier transforms infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), scanning electron microscope (SEM), and transmission electron microscope (TEM). The capability of the electron transfer rate on the surface of modified electrode evaluated is by electrochemical impedance spectroscopy (EIS). The square wave stripping voltammetry (SWSV) technique was employed to investigate the performance of chloroplatinum(II) complex-MWCNTs paste electrode for determination of mercury. Several operational parameters such as the composition ratios of the electrode, type of supporting electrolyte, pH of the solution, and the SWSV parameters were thoroughly investigated. Under optimal conditions, the linear range obtained was from 5.0 μM to 0.1 mM with limit detection of 3.7 μM. The interference from other heavy metals such as Ca 2+, Mg 2+, Ni 2+, Zn 2+, Cd 2+, Co 2+, Ba 2+, Mn 2+, and Ce 3+ did not influence the electrochemical response. The chloroplatinum(II) complex-MWCNTs paste electrode was successfully applied to determine mercury in skin lightening cosmetics with a good recovery (98.9%–101.1%).